Structural and Biochemical Characterization of Mycobacterium tuberculosis Zinc SufU-SufS Complex - Ingie Elchennawi; Philippe Carpentier; Christelle Caux; Marine Ponge; Sandrine Ollagnier de Choudens (Biomolecules, 2023)
Iron-sulfur (Fe-S) clusters are inorganic prosthetic groups in proteins composed exclusively of iron and inorganic sulfide. These cofactors are required in a wide range of critical cellular pathways. Iron-sulfur clusters do not form spontaneously in vivo; several proteins are required to mobilize sulfur and iron, assemble and traffic-nascent clusters. Bacteria have developed several Fe-S assembly systems, such as the ISC, NIF, and SUF systems. Interestingly, in Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), the SUF machinery is the primary Fe-S biogenesis system. This operon is essential for the viability of Mtb under normal growth conditions, and the genes it contains are known to be vulnerable, revealing the Mtb SUF system as an interesting target in the fight against tuberculosis. In the present study, two proteins of the Mtb SUF system were characterized for the first time: Rv1464(sufS) and Rv1465(sufU). The results presented reveal how these two proteins work together and thus provide insights into Fe-S biogenesis/metabolism by this pathogen. Combining biochemistry and structural approaches, we showed that Rv1464 is a type II cysteine-desulfurase enzyme and that Rv1465 is a zinc-dependent protein interacting with Rv1464. Endowed with a sulfurtransferase activity, Rv1465 significantly enhances the cysteine-desulfurase activity of Rv1464 by transferring the sulfur atom from persulfide on Rv1464 to its conserved Cys40 residue. The zinc ion is important for the sulfur transfer reaction between SufS and SufU, and His354 in SufS plays an essential role in this reaction. Finally, we showed that Mtb SufS-SufU is more resistant to oxidative stress than E. coli SufS-SufE and that the presence of zinc in SufU is likely responsible for this improved resistance. This study on Rv1464 and Rv1465 will help guide the design of future anti-tuberculosis agents.